ROLE OF Mn(TPP)Cl IN THE EPOXIDATION WITH SINGLET OXYGEN (Journal of Sciences, Islamic Republic of Iran)
Mn(TPP)Cl catalyzes cooxidation of olefin in the singlet oxygenation of sulfid. Mn(TPP)Cl is able to transfer an oxygen atom from a peroxidic intermediate generated in singlet oxygenation of sulfide to a metal ion affording metal 0x0 species which is responsible for epoxidation. This system leads to allcenes epoxidation such as styrene and cyclooctene. Epoxidation of cyclohexene produces cyclohexenol, cyclohexenone and cyclohexene oxide